Novel magnesium-based hydrogen storage alloy material and preparation method thereof

By increasing the content of magnesium in the magnesium-based hydrogen storage alloy and using composite coating materials to protect its surface, the problem that the magnesium-based hydrogen storage alloy is easily oxidized is solved, its cycle life and charge-discharge capacity are significantly improved, and high efficiency is achieved. Hydrogen storage and battery material properties.

CN119319246AInactive Publication Date: 2025-01-17CHENZHOU VOCATIONAL & TECH COLLEGE +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411428833.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Magnesium-based hydrogen storage alloys are easily oxidized, resulting in a short charge and discharge cycle life, affecting their performance in practical applications.

Method used

A new type of magnesium-based hydrogen storage alloy material MgxDyNi-TiaNib is used, with x>2 in its chemical formula. Amorphous alloy powder is prepared by ball milling in an argon atmosphere, and multi-mode distribution is formed through composite coating materials to protect the magnesium element on the alloy surface. , improve its antioxidant capacity.

Benefits of technology

It significantly improves the cycle life and charge and discharge capabilities of magnesium-based hydrogen storage alloys, achieves efficient hydrogen storage and battery material properties, and meets the needs of large-capacity mobile power supplies and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119319246A_ABST
    Figure CN119319246A_ABST
Patent Text Reader

Abstract

The invention provides a novel magnesium-based hydrogen storage alloy material and a preparation method thereof, and the chemical formula of the novel magnesium-based hydrogen storage alloy material is Mg < x > DyNi-Ti Ni < b, x > gt, y is equal to 0-1, 0 < = a < = 1, 0 < = b < = 1, a < = b and is not zero at the same time, MgxDyNi is a parent alloy, D is a doping element, and TiaNib is a coating material. The novel magnesium-based hydrogen storage alloy material prepared by the invention realizes high charge-discharge efficiency, long cycle life and high-stability tolerance elasticity for fast charge and fast discharge within a certain range, and meets the requirements of practical application on hydrogen storage alloys; the high-capacity mobile power supply can be widely applied to various electric vehicles needing high-capacity mobile power supplies, the field of communication information, energy storage systems of fuel cells, heat pumps, air conditioners, submarines, electric tools and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of power batteries, and in particular to a novel magnesium-based hydrogen storage alloy material and a preparation method thereof. Background Art

[0002] At present, sustainable clean energy includes solar energy, wind energy, ocean energy, geothermal energy, hydrogen energy, etc. However, no matter which energy is practical, the storage problem of these energy sources must be solved first. Therefore, the key to the development and utilization of new energy is to find new energy storage materials.

[0003] Among the numerous green energy sources, hydrogen energy has incomparable advantages. First, it has a large reserve. According to theoretical calculations, if all the hydrogen in seawater is extracted, the total heat generated will be more than 9,000 times the total heat released by all fossil fuels on the earth. Second, except for nuclear fuel, the calorific value of hydrogen is the highest among all fossil fuels, chemical fuels and biofuels, which is (1.21~1.43)×10 5 kJ / kgH 2 , which is 3 times the calorific value of gasoline, 4.5 times the calorific value of coke, and 4.7 times the calorific value of ethanol. Third, the product of hydrogen combustion is water, which is non-toxic and harmless. Fourth, hydrogen has a high ignition point, has a wide flammable range when mixed with air, and burns quickly, so hydrogen energy is a safe, convenient and efficient fuel.

[0004] There are many hydrogen storage materials. Compared with carbon nanomaterials, complexes and other energy storage materials, hydrogen storage alloys are a type of material that has attracted much attention due to its high energy storage density, low initial investment, abundant raw material resources, environmental friendliness, and stable safety performance. Among them, magnesium-based hydrogen storage alloys have become candidates for hydrogen storage materials due to their abundant resources, high hydrogen storage capacity, low initial investment, and environmental friendliness. What is even more attractive is that magnesium-based hydrogen storage alloys have a discharge capacity of up to 1000mA / g, and almost no element can match their volumetric storage capacity, making them an excellent material for new batteries that are more resistant to overcharge and over-discharge than lithium batteries and less prone to explosion in future battery materials. However, since magnesium-based hydrogen storage alloys are easily oxidized, the charge and discharge cycle life is affected, and many problems need to be solved before they can truly become practical. Summary of the invention

[0005] In view of the life problem of magnesium-based hydrogen storage alloys, the present invention provides a new type of hydrogen storage alloy material and a preparation method thereof, so as to improve the cycle life of magnesium-based hydrogen storage alloys and enable them to be put into practical application.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a novel magnesium-based hydrogen storage alloy material, the chemical formula of which is: Mg x Dy Ni-Ti a Ni b , x>2, y=0~1, 0≤a≤1, 0≤b≤1, a≦b and not zero at the same time, where Mg x D y Ni is the parent alloy, D is the doping element, Ti a Ni b For the covering material.

[0008] Cladding materialTi a Ni b According to the purpose of synthesizing alloys with good performance, according to the different compositions of the parent alloy, it can be coated with one material at a time, or it can be coated in two parts in batches, such as (TiNi) a -Ni (b-a) etc.

[0009] The present invention also provides a method for preparing the novel magnesium-based hydrogen storage alloy material, comprising:

[0010] 1) Press Mg x D y Ni、Ti a Ni b The powders of each element were weighed in the stoichiometric ratio shown in the figure, mixed evenly, and then ball-milled under an argon atmosphere to prepare Mg x D y Ni、Ti a Ni b Amorphous alloy powder;

[0011] 2) Press Mg x D y Ni-Ti a Ni b The designed amount of substance ratio is Mg x D y Ni、Ti a Ni b Amorphous alloy powder or Mg x D y Ni-(TiNi) a -Ni (b-a) The designed amount of substance ratio is Mg x D y Ni, TiNi amorphous alloy powder and Ni powder are mixed and ball-milled in an argon atmosphere to obtain the composite hydrogen storage alloy material.

[0012] Preferably, in steps 1) and 2), the powder of each element is analytically pure metal powder.

[0013] More preferably, the Mg powder is spherical atomized magnesium powder, which has high purity and good stability.

[0014] Preferably, in steps 1) and 2), the powder particle size of each element of the parent alloy is 100 mesh to 250 mesh, and the powder particle size of each element of the coating material is 160 mesh to 300 mesh.

[0015] Preferably, in steps 1) and 2), the ball mill is evacuated and filled with 1.0×10 5 Pa of argon to prevent the alloy metal powder from being oxidized.

[0016] Preferably, in step 1), the ball milling is performed intermittently, the ball-to-material ratio is 8:1 to 50:1, the ball milling speed is 300 to 1200 rpm, and the Mg x D y The ball milling time of Ni is 30 to 140 hours; the ball milling time of TiNi is 5 to 80 hours.

[0017] Preferably, in step 2), the ball milling is intermittent ball milling, with a ball-to-material ratio of 10:1 to 50:1, a ball milling speed of 300 to 1200 rpm, and a ball milling time of 10 to 90 hours.

[0018] The beneficial effects of the present invention are as follows:

[0019] First, the traditional idea of ​​preparing magnesium-based hydrogen storage alloys by uniformly distributing magnesium and nickel in the A2B dosing method was broken, and the content of magnesium in the parent alloy was greatly increased to greater than 2, so that the new magnesium-based hydrogen storage alloy contains more active element magnesium, providing the most fundamental element guarantee for long-term and effective hydrogen and electricity storage. At the same time, the Mg between the doping element D (which can be any one or several elements in the periodic table) and magnesium was broken. 2-y D y Relationship. The amount of Mg element and the amount of doping elements are independent of each other and are adjusted independently according to the goal of preparing better battery materials. In the new magnesium-based hydrogen storage alloy material prepared by the present invention, the Mg element is distributed in a gradient, and the anti-oxidation coating material greatly protects the magnesium element on the surface of the alloy, which changes the situation that the magnesium element on the surface of the A2B-type magnesium-based hydrogen storage alloy is easily oxidized, powdered and fallen off, and Mg is easily lost, resulting in a significantly lower performance of the magnesium-based hydrogen storage alloy material, and the cycle life of the electrode when used as a battery material will be rapidly shortened.

[0020] Secondly, in order to improve the ability of the alloy surface to exchange current, a composite coating material was developed to form a multi-mode, evenly distributed active site for charging and discharging of hydrogen storage alloys, which greatly improved the charging and discharging capacity of magnesium-based hydrogen storage alloys. Specifically, Mg is an active metal with strong hydrogen storage capacity, which is easily oxidized to form MgO. The structure of MgO is relatively loose, which can easily cause the alloy to pulverize and fall off, resulting in a reduction in the hydrogen storage element Mg in the hydrogen storage alloy and a reduction in the storage capacity of the alloy. Ti is also an element with a certain hydrogen storage capacity, but it is difficult to react with oxygen. After reacting with oxygen, a dense oxide is generated. If Ni and Ti form an alloy or solid solution, the activity of Ti in exchanging charges will also be increased. Coating this alloy or solid solution on the surface of the magnesium-based hydrogen storage alloy will, on the one hand, protect the magnesium-based hydrogen storage alloy from or reduce oxidation; on the other hand, more active sites for exchanging charges will be formed on the surface of the alloy, thereby effectively improving the charging and discharging capacity and antioxidant capacity of the magnesium-based hydrogen storage alloy. The present invention utilizes the property that Mg and Ni, Ti and Ni are easy to form alloys, and forms magnesium-based and Ti-Ni hydrogen storage alloys respectively, and prepares a mixed amorphous hydrogen storage alloy similar to the earth structure, with an easily oxidized alloy inside and an anti-oxidation alloy coated outside. This type of hydrogen storage alloy completely changes the cycle characteristic curve of magnesium-based hydrogen storage alloys, and achieves high-rate charge and discharge efficiency, high cycle life, and high and stable tolerance elasticity to fast charge and discharge at different current densities within a certain range, meeting the requirements of practical applications for hydrogen storage alloys.

[0021] The novel magnesium-based hydrogen storage alloy material prepared by the present invention can be widely used in various electric vehicles requiring large-capacity mobile power sources, communication information fields, fuel cell energy storage systems, as well as heat pumps, air conditioners, submarines, electric tools, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 .Cycling characteristic curves of the materials prepared by the present invention and the traditional method (charging at 800mA / g for one hour).

[0023] Figure 2 Mg of the present invention x D y Ni-Ti a Ni b Cyclic characteristic curves of materials prepared with different x values.

[0024] Figure 3 .Comparison of high rate performance of materials prepared by the present invention and traditional methods.

[0025] Figure 4 . Mg4Ni-(TiNi) of the present invention a -Ni (b-a) Discharge efficiency of discharges at different current densities.

[0026] Figure 5 .Mg3Si of the present invention 0.35 Ni-Ti a Ni b Discharge efficiency retention rate at different current densities.

[0027] Figure 6 . Mg3C of the present invention 0.4 Ni-Ti a Ni b Coulombic efficiency of high-rate charging and high-rate discharging. DETAILED DESCRIPTION

[0028] In order to explain the present invention more clearly, the present invention is further described in detail below in conjunction with embodiments and with reference to the accompanying drawings. It should be understood by those skilled in the art that the content described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0029] Example 1

[0030] This example provides a comparison between alloys prepared by geotectonic methods and alloys prepared by traditional methods.

[0031] According to the chemical formula of Mg2Ni (prepared twice) and Mg3Ni of the earth construction method, each element required for preparing 10g of the parent alloy of each material was accurately weighed and placed in a stainless steel vacuum tank, stainless steel grinding balls were added, and the ball-to-material ratio was 40:1. The vacuum was evacuated and filled with argon three times. The ball milling speed was 400rpm, and the operation was 1.0h and the rest time was 12min, and 50 cycles were run.

[0032] Open the vacuum tank in the glove box and weigh according to the traditional method according to the coating ratio of Mg2Ni:Ni=1:1 and Mg2Ni:Ni=1:1.2.

[0033] The earth's structural law is to prepare the coating material Ti a Ni b (a = 0.004, b = 0.016) was added to Mg3Ni, whose Mg element composition is much greater than that of the magnesium-based hydrogen storage alloy Mg2Ni, according to the molar ratio of Mg3Ni:Ti a Ni b =1:1 to add coating elements. The grinding balls are supplemented at 30:1. Continue to run 20 cycles in the same intermittent mode.

[0034] Take out the sample from the glove box and test the charge and discharge capacity on the Blue Power CT2001A battery test system. Collect the data and plot it as shown in the figure. Figure 1 .

[0035] Depend on Figure 1It can be seen that the alloy prepared by the method of the present invention (geo-tectonic method) has better discharge capacity, and the discharge capacity at 20 cycles is 2.5 times and 3.4 times that of the material prepared by the traditional method. It can also be seen that under the premise of maintaining high discharge capacity, the material prepared by the present invention has better stability.

[0036] Example 2

[0037] This embodiment provides Mg x D y Ni:Ti a Ni b =1:1.2, the doping element D is Zr, y=0.2, a=0.004, b=0.016, and x are 1.8, 2.0, 2.3, 2.7, 3.0, 3.5 and 4.0 respectively.

[0038] According to the chemical formula corresponding to different values ​​of x, accurately weigh the elements required to prepare 10g of the parent alloy of each material and place them in a stainless steel vacuum tank. Add stainless steel grinding balls with a ball-to-material ratio of 40:1, and evacuate and fill with argon three times. Run 50 cycles with a ball mill speed of 400rpm, 1.0h operation and 12min interval. Open the vacuum tank in the glove box, add the coating material according to the chemical formula and replenish the grinding balls at a ratio of 30:1. Continue to run for 20 cycles with the same intermittent operation mode. Take out the sample in the glove box and test the charge and discharge capacity on the Blue Electric Battery Test System. Collect the data and draw a graph as shown Figure 2 .

[0039] Figure 2 and Figure 1 By comparison, it can be found that after 20 charge and discharge cycles, even if the x value conforms to the traditional measurement relationship such as the black line, the discharge specific capacity of the material using the earth construction method is Figure 1 The discharge capacity of the materials prepared by the earth construction method is 1.8 times and 1.4 times that of the materials prepared by the two traditional methods. It can be seen that no matter what x is, the discharge capacity of the materials prepared by the earth construction method is relatively high. At the same time, the materials with flatter characteristic curves are the materials with higher cycle stability.

[0040] Mg2Ni-Ti a Ni b ,Mg 2.3 Zr 0.2 Ni-Ti a Ni b ,Mg3Zr 0.2 Ni-Ti a Ni bThe three materials were charged and discharged at 800mA / g for one hour, and then discharged at 400mA / g, 800mA / g, 1200mA / g, and 1600mA / g, respectively. The percentage of the obtained discharge capacity to 800mAh / g is called the high-rate discharge capacity. Figure 3 .

[0041] Depend on Figure 3 It can be seen that the material Mg prepared by the present invention 2.3 Zr 0.2 Ni-Ti a Ni b ,Mg3Zr 0.2 Ni-Ti a Ni b The high rate discharge performance is much higher than that of the alloy Mg2Ni-Ti prepared by traditional methods. a Ni b This shows that the geotectonic method increases the Mg content in the parent alloy and dopes Zr, which has a larger atomic radius and stronger oxidation resistance and effective nuclear power than Mg, effectively enhancing the stability of the parent alloy. At the same time, a large proportion of Ti, which has catalytic activity for electron exchange and has certain hydrogen storage alloy properties, a Ni b The coating material can not only realize the gradient distribution of Mg element, but also Mg is well protected in a stable environment with more charge and discharge active sites, realizing long-term and effective charge and discharge cycle. The geotectonic method improves the initial discharge capacity, cycle life and high-rate charge and discharge capacity of magnesium-based hydrogen storage alloys to an unprecedented level. The battery material prepared by the present invention has stronger competitiveness as a vehicle battery. Starting, accelerating and climbing are faster and more powerful.

[0042] Example 3

[0043] This embodiment provides Mg4Ni-(TiNi) a -Ni (b-a) Preparation of composite alloys.

[0044] Mg (100 mesh), Ti (200 mesh), and Ni (250 mesh) metal powders were mixed evenly according to the stoichiometric ratio of Mg4Ni and TiNi, and were placed in a stainless steel vacuum ball jar with a volume of 300 mL, with a total mass of 8 g and a ball-to-material ratio of 40:1. Stainless steel balls were placed in the jar. Before ball milling, the jar was evacuated and filled with 1.0×10 5 Pa of argon gas was used to prevent the alloy metal powder from being oxidized. The ball milling speed was 550 rpm and the ball milling time was 140 hours. The working system adopted intermittent rotation to prevent the amorphous alloy from re-crystallizing due to excessive temperature rise.

[0045] By Mg4Ni:Ti a Ni a :Ni (b-a) =1:(48.867+58.693)a:58.693(ba) weight ratio was added into the ball mill (a=0.002, b=0.018). The ball mill was first evacuated and filled with 1.0×10 5 Pa of argon was used to prevent the metal powder from being oxidized. The powder was ball milled at 300 rpm for 10 hours. The product was taken out from the glove box and passed through a 200 mesh sieve.

[0046] Weigh 0.1000g alloy powder accurately on an analytical balance, add 0.3000g carbonyl nickel powder and mix evenly, make slices, weld the tabs, and use the CT2001A battery test system of Wuhan Blue Electric Electronics Co., Ltd. to test the alloy charge and discharge performance. The charge and discharge system is 1000mA / g for 0.5 hours, and the charge and discharge coulomb efficiency is 200mA / g, 400mA / g, and 800mA / g respectively. Figure 4 shown.

[0047] The results show that after rapid charging with a large current, the charge and discharge coulomb efficiency of the material remains almost unchanged at 98% regardless of the current density at which it is discharged. This shows a fact: the magnesium-based hydrogen storage alloy prepared by the present invention is an excellent battery material with good charge and discharge capabilities and a long life.

[0048] Example 4

[0049] This embodiment provides Mg3Si 0.35 Ni-Ti a Ni b That is, Mg x D y Ni-Ti a Ni b The doping element D is Si, y=0.35, a=0.003, b=0.015, Mg3Si 0.35 Ni:Ti a Ni b =1:1.2.

[0050] Mg (100 mesh), Ti (200 mesh), Ni (250 mesh) metal powders were respectively pressed into Mg3Si 0.2 Ni and TiNi were mixed evenly in a stoichiometric ratio and placed in a stainless steel vacuum ball tank with a volume of 300 mL. The total mass was 8 g, and the ball-to-material ratio was 45:1. Stainless steel balls were placed in the ball mill tank. Before ball milling, the ball mill tank was evacuated and filled with 1.0×10 5Pa of argon gas to prevent the alloy metal powder from being oxidized. The ball milling speed is 450rpm and the ball milling time is 100 hours. The working system adopts intermittent rotation to prevent the amorphous alloy from re-crystallizing due to excessive temperature rise.

[0051] Mg3Si 0.35 Ni and Ti a Ni b Add 4 g of 20% NH4CO3 into the stainless steel mill in a ratio of 1:1.2. First, evacuate the ball mill and fill it with 1.0×10 5 Pa of argon gas was used to prevent the metal powder from being oxidized. The powder was ball milled at 350 rpm for 10 hours. The product was taken out and passed through a 200 mesh sieve.

[0052] Weigh 0.1000g alloy powder accurately on an analytical balance, add 0.3000g carbonyl nickel powder and mix evenly, make slices, weld the tabs, and use the CT2001A battery test system of Wuhan Blue Electric Electronics Co., Ltd. to test the alloy charge and discharge performance. The charge and discharge system is 1200mA / g for 0.5 hours, and the charge and discharge coulomb efficiency is 200mA / g, 400mA / g, and 800mA / g respectively. Figure 5 shown.

[0053] The results show that after rapid charging with a large current, the charge and discharge coulomb efficiency of the material remains almost unchanged at 98% regardless of the current density at which it is discharged. This shows a fact: the magnesium-based hydrogen storage alloy prepared by the present invention is an excellent battery material with good charge and discharge capabilities and a long life.

[0054] Example 5

[0055] This embodiment provides Mg3C 0.4 Ni-Ti a Ni b That is, Mg x D y Ni-Ti a Ni b In the embodiment, the doping element D is C, x=3, y=0.4, a=0.004, b=0.02.

[0056] Mg (100 mesh), Ti (200 mesh), and Ni (250 mesh) metal powders were respectively mixed into Mg3C 0.4 Ni and TiNi are uniformly mixed in a stoichiometric ratio (in this embodiment, C uses microcrystalline graphite, regardless of brand and model), and are placed in a stainless steel vacuum ball tank with a volume of 300 mL, with a total mass of 8 g and a ball-to-material ratio of 30:1. Stainless steel balls are placed in the ball mill tank. Before ball milling, the ball mill tank is evacuated and filled with 1.0×10 5Pa of argon gas to prevent the alloy metal powder from being oxidized. The ball milling speed is 400 rpm and the ball milling time is 100 hours. The working system adopts intermittent rotation to prevent the amorphous alloy from re-crystallizing due to excessive temperature rise.

[0057] Mg3C 0.4 Ni, Ti a Ni b Add to the stainless steel grinding jar, the total mass is 4g. First, evacuate the ball mill and fill it with 1.0×10 5 Pa of argon was used to prevent the metal powder from being oxidized. The powder was ball milled at 300 rpm for 10 hours. The product was taken out from the glove box and passed through a 200 mesh sieve.

[0058] Weigh 0.1000g alloy powder accurately on an analytical balance, add 0.3000g carbonyl nickel powder and mix evenly, make slices, weld the tabs, and use the CT2001A battery test system of Wuhan Blue Electric Electronics Co., Ltd. to test the alloy charge and discharge performance. The charge and discharge system is 1000mA / g for 0.25 hours, and the charge and discharge coulomb efficiency of 800mA / g is as follows: Figure 6 shown.

[0059] The results show that the material has good cycling stability in the fast charging and high-rate discharge states, and the coulombic efficiency remains stable after 1000 cycles.

[0060] Obviously, the above embodiments of the present invention are merely examples to more clearly illustrate the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A new type of magnesium-based hydrogen storage alloy material, whose chemical formula is: Mg x D y Ni-Ti a Ni b , x>2, y=0~1, 0≤a≤1, 0≤b≤1, a≦b and they are not zero at the same time, where, Mg x D y Ni is the parent alloy, D is the doping element, Ti a Ni b For the covering material.

2. A method for preparing a novel magnesium-based hydrogen storage alloy material according to claim 1, comprising: 1) Press Mg x D y Ni、Ti a Ni b The powders of each element were weighed in the stoichiometric ratio shown in the figure, mixed evenly, and then ball-milled under an argon atmosphere to prepare Mg x D y Ni、Ti a Ni b Amorphous alloy powder; 2) Press Mg x D y Ni-Ti a Ni b The designed amount of substance ratio is Mg x D y Ni、Ti a Ni b Amorphous alloy powder or Mg x D y Ni-(TiNi) a -Ni (b-a) The designed amount of substance ratio is Mg x D y Ni, TiNi amorphous alloy powder and Ni powder are mixed and ball-milled in an argon atmosphere to obtain the composite hydrogen storage alloy material.

3. The preparation method according to claim 2, characterized in that: In steps 1) and 2), the powder of each element is analytically pure metal powder.

4. The preparation method according to claim 2 or 3, characterized in that: Mg powder is spherical atomized magnesium powder.

5. The preparation method according to claim 2, characterized in that: In steps 1) and 2), the powder particle size of each element of the parent alloy is 100 mesh to 250 mesh, and the powder particle size of each element of the coating material is 160 mesh to 300 mesh.

6. The preparation method according to claim 2, characterized in that: In steps 1) and 2), the ball mill was evacuated and filled with 1.0×10 5 Pa of argon to prevent the alloy metal powder from being oxidized.

7. The preparation method according to claim 2 or 6, characterized in that: In step 1), the ball milling is performed in an intermittent manner, the ball-to-material ratio is 8:1 to 50:1, the ball milling speed is 300 to 1200 rpm, and the Mg x D y The ball milling time of Ni is 30 to 140 hours; the ball milling time of TiNi is 5 to 80 hours.

8. The preparation method according to claim 2 or 6, characterized in that: In step 2), the ball milling is intermittent ball milling, the ball-to-material ratio is 10:1-50:1, the ball milling speed is 300-1200 rpm, and the ball milling time is 10-90 hours.